Mannan-binding lectin plasma levels in leprosy: deficiency confers protection against the lepromatous but not the tuberculoid forms - Dornelles, LN (Blackwell Science Inc, 2006)
Mannan-binding lectin (MBL) is an important component of the first-line defence against infections. Evidence has shown that MBL deficiency, reducing phagocytosis and internalization of intracellular pathogens may protect the host against intracellular infections such as leprosy. In this study, we speculated whether genetically determined low MBL serum levels confer protection against Mycobacterium leprae infection. One hundred and ninety-one patients with leprosy, presenting lepromatous (n = 118), tuberculoid (n = 31), dimorph (n = 30) and indeterminate (n = 12) clinical forms and 110 healthy controls matched with the patients according to sex, age and ethnic background were investigated. MBL concentrations were measured in a double-antibody enzyme immune assay and C-reactive protein (CRP) serum levels by nephelometry. A significant negative association of MBL low values (< 100 ng/ml) was observed with lepromatous patients when comparing with controls and tuberculoid patients [10/118, 8·47% versus 21/110, 19·09% P = 0·03 χ(2) with Yates' correction, odds ratio (OR) 0·39, confidence interval (CI) 0·18–0·88 and 8/31, 25·81%, P = 0·02, OR 0·27, CI 0·09–0·75, respectively]. There was no significant difference in the distribution of MBL levels between patients and controls or among the clinical forms. The concentration of CRP was significantly increased in the patients (P = 0·0002) and in the lepromatous form (P = 0·0001) when compared to controls. A weak positive correlation between MBL and CRP levels was observed in the patients (P = 0·010, R = 0·255). These data suggest a protective role for MBL deficiency against the development of the most severe and multi-bacillary form of leprosy.